Domination and the arts of resistance: hidden transcript - Parlak, Fatmanur; Islam, Mozharul; Rahman, Mazhar İslam (Selçuk Üniversitesi, 2022)
This review critically analyzes James Scott's book, Domination and the Arts of Resistance. Scott's account explores the mysteries of unequal power relations in society and the reflection of human behavior in the intellectual world. The book examines the reflections of people's positions on their actions in social life. In addition, by producing new concepts such as public and hidden transcripts, the author contributes to the process of social interpretation. Based on these concepts, Scott tries to analyze why people behave differently in different environments and examine these behaviors' motives. In this way, he explains that the emotions that people involuntarily reflect in some extraordinary situations come from these hidden urges. Within the scope of this book review, we analyzed the book based on Scott's strategies for advancing this scholarship and the relationships in our daily lives. We also tried to emphasize the importance of the book reflected in human life and observed in the social sphere.

Bu inceleme, James Scott'ın Hakimiyet ve Direniş Sanatları kitabını eleştirel bir şekilde analiz etmektedir. Scott'ın anlayışına göre kitapta, toplumsal alanda bulunan eşitsizlik ilişkilerinin gizemleri ve bunun insan davranışının entelektüel dünyasındaki yansımaları incelenerek keşfedilmeye çalışılmaktadır. Kitap, insanların sahip oldukları konumlarının toplumsal hayattaki eylemlerine yansımalarını inceler. Ayrıca yazar kitapta, kamusal ve gizli transkript gibi yeni kavramlar üreterek toplumsal alanı yorumlama sürecine katkıda bulunur. Scott, bu kavramlara dayanarak, insanların farklı ortamlarda neden farklı davrandıklarını analiz etmeye çalışır ve bu davranışların arkasında yatan güdüleri inceler. Bu şekilde, insanların bazı olağanüstü durumlarda istemsizce yansıttıkları duyguların, bu gizli dürtülerden kaynaklandığını açıklamaya çalışır. Bu kitap incelemesi kapsamında bizler de Scott'ın kitabını oluşturma stratejilerini ve günlük hayatımızdaki ilişkileri baz alarak kitabın analizini oluşturduk ve kitabın insan hayatına yansıyan ve toplumsal alanda gözlemlenebilen önemini vurgulamaya çalıştık.
Keywords: Domination; Arts of resistance; Public transcript; Hidden transcript; Power relations; Egemenlik; Direniş sanatları; Kamu deşifresi; Gizli deşifre; İktidar ilişkileri